Ichthyofaunal Diversity Of Jammu Region Of North Western Himalaya And Its Conservation Status (Applied Biological Research, 2023)
Jammu and Kashmir has enormous fisheries potential due to its vast area and  quantity of freshwater sources. The UT has rivers like Chenab, Tawi, Ravi,  and Jhelum, as well as lakes including Dal lake, Wular lake, Manasbal lake,  and Surinsar, Manasar lake. The purpose of this study is to summarize some  of the key studies done on the Ichthyofaunal diversity of numerous water  bodies in the Jammu region, as well as to create an inventory of the region's  Ichthyofauna while analyzing the dominant and least prominent species. The  examination undertaken revealed the presence of 158 distinct fish species  belonging to 10 orders, with Cypriniformes being the most dominating order  and Cyprinidae being the most significant contributing family, while  Anabantiformes and Clupeiformes were in traces. Furthermore, analysis of  conservation status of the fauna revealed that, majority of the species in the  region have a conservation status of "Least Concern", while a few species are  endangered or vulnerable. Analysis of fish fauna of the region's major lotic  water bodies finds that river Ravi has the largest fish diversity; however, a  comparative analysis of fish fauna reveals that diversity is diminishing in the  region necessitating extensive conservation strategies.
Keywords: Conservation; cypriniformes; fish diversity; , Jammu rivers